FRI0389 Primary Sjögren's Syndrome and Occupational Risk Factors: A Case–Control Study. (9th June 2015) - Chaigne, B.; Lasfargues, G.; Marie, I.; Hüttenberger, B.; Lavigne, C.; Marchand-Adam, S.; Maillot, F.; Diot, E.
Abstract : Background: Primary Sjögren's syndrome (pSS) is a systemic autoimmune disease characterized by eye and mouth dryness and lymphocytic infiltration of the salivary glands. Although the pathogenesis of pSS is more clearly understood, its aetiology is still unknown. As for other autoimmune diseases, pSS is associated with specific genetic background, impaired immune response and environmental factors (1). However, only a few of them have been identified in pSS. Occupational exposure to silica is known to be associated with autoimmune diseases such as systemic sclerosis and systemic lupus erythematosus (2-5). Therefore we hypothesized that occupational risks factors are associated with pSS. Objectives: A case–control study was carried out to investigate the relation between primary Sjögren's syndrome (pSS) and occupational exposure. Methods: One hundred seventy five cases of pSS admitted consecutively into the internal medicine departments of three French university hospitals from 2010 to 2013 were included. For each case, two age and gender matched controls were selected during the same period in the same departments. Occupational exposure was assessed retrospectively by industrial hygienists and occupational practitioners. Exposure to occupational factors such as organic solvents or silica was investigated using semiquantitative estimates of exposure. An exposure score was calculated for each subject based on probability, intensity, daily frequency, and duration of exposure for each period of employment. The final cumulative exposure score was obtained, taking into account all periods of employment. Results: Significant associations with pSS were observed for dichloromethane (OR 9.28, 95%CI 2.60-33.03), perchlorethylene (OR 2.64, 95%CI 1.20-5.77) chlorinated solvents (OR 2.95, 95%CI 1.77-4.93), benzene (OR 3.30, 95%CI 1.07-10.26), toluene (OR 4.18 95%CI 1.41-12.43), white spirit (OR 3.60, 95%CI 1.39-9.33), aromatic solvents (OR 3.03, 95%CI 1.41-6.50) and any types of solvents (OR 2.76, 95%CI 1.70-4.47). Risk of pSS was significantly associated with a high cumulative exposure score of occupational exposure to toluene (OR 4.69, 95%CI 1.42-15.45), white spirit (OR 3.30, 95%CI 1.07-10.26), aromatic solvents (OR 2.50, 95%CI 1.06-5.91) and any types of solvents (OR 2.25, 95%CI 1.20-4.22). Conclusions: This work suggests the influence of occupational risk factors in the occurrence of pSS. References: Martel C et al. [Pathophysiology of primary Sjögren's syndrome.]. Rev Med Interne. 2014 Jan 7; Diot E et al. Systemic sclerosis and occupational risk factors: a case-control study. Occup Environ Med. 2002 Aug;59(8):545–9. Cooper GS et al. Occupational and environmental exposures and risk of systemic lupus erythematosus: silica, sunlight, solvents. Rheumatology (Oxford). 2010 Nov;49(11):2172–80. Marie I et al. Prospective study to evaluate the association between systemic sclerosis and occupational exposure and review of the literature. Autoimmun Rev. 2014 Feb;13(2):151–6. Czirják L, Kumánovics G. Exposure to solvents in female patients with scleroderma. Clin Rheumatol. 2002 May;21(2):114–8. Disclosure of Interest: None declared